Has human capital accounted for regional economic growth in Italy? A panel analysis on the 1980-2001 period - Eliana Baici; Giorgia Casalone (European Regional Science Association (ERSA), 2005)
Since Solow's (1957) contribution, human capital entered in the debate on economic growth as a leading long period development factor. If from a theoretical point of view the role of human capital on economic growth both directly or throughout its use in the R&D activities is fully accepted, from an empirical perspective the results are much more controversial, strictly depending on the quality of data. A recent analysis by Aghion and Cohen (2004) put in evidence that high-level human capital has a positive effect on economic performance only if a country is close to the technological frontier: countries that are far from this frontier, specialised in traditional sectors, can growth, almost in the short run, even exploiting medium-level human capital. This analysis induce at looking at the link between human capital and growth with a greater detail, trying to disclose the effect of different human capital levels in a country, such as Italy, traditionally oriented toward a low/medium technology production. Using, beyond the usual proxies of human capital, some measures of its quality and of its interrelation with R&S sector, we would like to give a new contribution to the analysis of regional growth in Italy in the period 1980-2001. The panel approach, here used, allows us to take account of the temporal variability and to check for omitted variable specific for regions and persistent over time.
Keywords: 330